2021
DOI: 10.3390/pr9020317
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Expression of Levansucrase Gene of Bacillus velezensis BM-2 and Enzymatic Synthesis of Levan

Abstract: Levan is a versatile and valuable fructose homopolymer, and a few bacterial strains have been found to produce levan. Although levan products have numerous specific functions, their application and promotion were limited by the production capacity and production cost. Bacillus velezensis BM-2 is a levan-synthesizing strain, but its levan production is too low to apply. In this study, the levansucrase gene of B. velezensis BM-2 was cloned to plasmid pET-32a-Acma-zz, and the recombinant plasmids were transferred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…In accordance with these results, the following experiments (the effects of nitrogen and carbon sources on EPS production) were conducted with an initial pH of 6.5. The EPS production profile during SmF at different initial pH values may be because EPS synthesis depends on the action of an extracellular enzyme that has a catalytic response to pH changes, directly impacting EPS yields [ 19 ]. As shown in Figure 2 , the highest EPS concentration was obtained in the production system implemented in the present investigation when the initial pH of the SmF was adjusted to 6.5.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In accordance with these results, the following experiments (the effects of nitrogen and carbon sources on EPS production) were conducted with an initial pH of 6.5. The EPS production profile during SmF at different initial pH values may be because EPS synthesis depends on the action of an extracellular enzyme that has a catalytic response to pH changes, directly impacting EPS yields [ 19 ]. As shown in Figure 2 , the highest EPS concentration was obtained in the production system implemented in the present investigation when the initial pH of the SmF was adjusted to 6.5.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, the results are consistent with the results obtained by Zhang et al [ 55 ], who reported a maximum EPS yield when 300 g/L of sucrose was used as a carbon source with Bacillus methylotrophicus . Furthermore, the EPS yield decreased significantly above this sucrose concentration, probably because of the increase in viscosity and an enzymatic inhibition that consequently impacted EPS synthesis [ 19 , 41 ]. On the other hand, the use of recombinant yeasts for levan production has been reported; e.g., Ko et al [ 29 ] reported a levansucrase from Rahnella aquatilis expressed in Saccharomyces cerevisiae , obtaining yields of 3.17 g/L/h.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main chain is branched through the β-(2 → 1) linkage of the fructofuranosyl rings ( Mendonça et al, 2021 ). The production of levan starts in the extracellular medium through the conversion of sucrose to fructose/glucose by the enzyme SacB, which synthesizes fructose polymers through a transfructosylation reaction using sucrose as a donor fructose/glucose ( Xu et al, 2021 ). The production of levan has already been described in other Paenibacillus species, such as P. polymyxa DSM 365 ( Okonkwo et al, 2020 ), Paenibacillus sp.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular dockings with the enzymes LevG and InuGB from L. gasseri had a percentage of sequence identity of 2YFS.1.A greater than 62%, and couplings with binding energies greater than -7.0 kcal/mol for agavins of a low degree of polymerization. Compared with this study, tridimensional structures of levansucrase from proteobacteria Sphingobium chungbukense DJ77, Zymomonas mobilis and Bacillus amyloliquefaciens levansucrase KK9 with 34%, 54% and 89% of sequence identity have been employed (Xu et al, 2021). When B. amyloliquefaciens KK9 levanetype fructooligosaccharides were used, affinity energy of -7.7 kcal/mol was obtained (Phengnoi et al, 2020).…”
Section: Discussionmentioning
confidence: 95%